2014
DOI: 10.3389/fpls.2014.00014
|View full text |Cite
|
Sign up to set email alerts
|

Functions and regulation of quorum-sensing in Agrobacterium tumefaciens

Abstract: In Agrobacterium tumefaciens, horizontal transfer and vegetative replication of oncogenic Ti plasmids involve a cell-to-cell communication process called quorum-sensing (QS). The determinants of the QS-system belong to the LuxR/LuxI class. The LuxI-like protein TraI synthesizes N-acyl-homoserine lactone molecules which act as diffusible QS-signals. Beyond a threshold concentration, these molecules bind and activate the LuxR-like transcriptional regulator TraR, thereby initiating the QS-regulatory pathway. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 112 publications
(168 reference statements)
0
92
0
1
Order By: Relevance
“…Interestingly, a fadL homolog was not found in Bradyrhizobiaceae. Bradyrhizobium japonicum was reported to produce unusual isovaleryl-HSL QS signals (30) whereas A. tumefaciens QS involves AHLs with C 6 or C 8 acyl chains (27). Thus, we speculate that species synthesizing AHLs with acyl chains of 14 or more carbons, or coming into contact with species producing them, might have evolved FadL to facilitate their sensing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a fadL homolog was not found in Bradyrhizobiaceae. Bradyrhizobium japonicum was reported to produce unusual isovaleryl-HSL QS signals (30) whereas A. tumefaciens QS involves AHLs with C 6 or C 8 acyl chains (27). Thus, we speculate that species synthesizing AHLs with acyl chains of 14 or more carbons, or coming into contact with species producing them, might have evolved FadL to facilitate their sensing.…”
Section: Discussionmentioning
confidence: 99%
“…S6). Because these bacteria use AHL-based QS (8,(25)(26)(27), we asked whether promotion of long-chain AHL sensing is a common trait of their FadL proteins. For this, fadL homologs from these species were ectopically expressed in the S. meliloti sinI fadL mutant by introduction of plasmid-localized heterologous fadL genes driven by an IPTG-inducible lac promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Agrobacterium tumefaciens is a well known plant pathogen, which efficiently utilizes the QS apparatus to accomplish the process of conjugation and virulencecrown gall tumors [124,125]. A. tumefaciens embodies the tumor-inducing plasmid designated as Ti plasmid which harbours the virulent genes.…”
Section: Agrobacteriummentioning
confidence: 99%
“…Indeed, it has been shown that Agrobacterium tumefaciens cells carrying conjugative Ti plasmids show a donor-density-dependent increase in transfer, which is mediated by an extracellular quorum-sensing acyl-homoserine lactone autoinducer synthesized by the plasmid-encoded TraI autoinducer synthetase (45,46). In contrast, we have demonstrated that high donor density reduced the frequency of pheromone-controlled conjugative transfer of plasmids pAD1 and pAM373 in E. faecalis.…”
Section: Discussionmentioning
confidence: 55%